2009
DOI: 10.29173/cjs4198
|View full text |Cite
|
Sign up to set email alerts
|

Culture and class in Canada

Abstract: I apply Pierre Bourdieu’s conception of relationally-defined social spaces of capitals and classes that delimit highbrow and lowbrow cultural forms to Canadian society. I use categorical principal components analysis techniques and a nationally representative survey dataset from 1998 containing measures of economic capital, cultural capital and a wide range of cultural practices to construct a visual representation of Canadian social space which is directly inspired by the social space for 1960s France crafted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 37 publications
(25 reference statements)
5
41
0
1
Order By: Relevance
“…First, the Caucasians who identified such interests may have been more affluent, which is possible given that studies show that Caucasians, particularly those born in Canada, earn more than Canadian-born visible minorities and immigrants (Pendakur and Pendakur 2011; Statistics Canada 2014 a ). Previous research found that attendance at cultural events like the theatre is associated with income and educational attainment (Veenstra 2010), which suggests that better access to educational and economic capital could grant admission to cultural capital. Second, Caucasians might have been more likely than older people from the other racial/ethnic groups to perceive high-end cultural practices as increasing their attractiveness.…”
Section: Discussionmentioning
confidence: 99%
“…First, the Caucasians who identified such interests may have been more affluent, which is possible given that studies show that Caucasians, particularly those born in Canada, earn more than Canadian-born visible minorities and immigrants (Pendakur and Pendakur 2011; Statistics Canada 2014 a ). Previous research found that attendance at cultural events like the theatre is associated with income and educational attainment (Veenstra 2010), which suggests that better access to educational and economic capital could grant admission to cultural capital. Second, Caucasians might have been more likely than older people from the other racial/ethnic groups to perceive high-end cultural practices as increasing their attractiveness.…”
Section: Discussionmentioning
confidence: 99%
“…In the weak form of the homology thesis, the space of positions and the spaces to which it is homologous are not configured in as complicated a manner. For instance, while evidence suggests that the sum total of economic capital and cultural capital structures the primary dimension of the social spaces of contemporary France (Coulangeon and Lemel 2007), Canada (Veenstra 2010), Finland (Kahma and Toikka 2012), and the United Kingdom (Gayo-Cal et al 2006;Le Roux et al 2008) as well as France of the 1960s (Bourdieu [1979(Bourdieu [ ] 1984, the relative composition of these capitals does not appear to contribute to structuring the social spaces of contemporary France (Coulangeon and Lemel 2007), Finland (Kahma and Toikka 2012), and the United Kingdom (Gayo-Cal et al 2006;Le Roux et al 2008). If one capital or the sum of several capitals effectively delineates class positions then the weak form of the homology thesis is evident and nonrelational techniques such as regression analysis are presumably up to the task of uncovering a homology between positions and tastes.…”
Section: The Bourdieusian Homology Frameworkmentioning
confidence: 99%
“…Other scholars have already investigated these fields, in various national contexts, providing valuable insights into their character, especially in regards to the array of capitals at stake within them. For example, the sum total of economic capital in the form of wealth and institutionalised cultural capital in the form of educational credentials appears to structure the primary dimension of the field of power, the dimension along which social classes are presumably arrayed, in France of the 1960 to 1970s (Bourdieu 1984), Canada of 1998 (Veenstra 2010), France of 2003(Coulangeon and Lemel 2009) and the UK in 2003(Le Roux et al 2008. The relative composition of wealth and educational credentials also seemingly contributed to structuring the French field of power of the 1960 and 1970s (Bourdieu 1984) and Canada in 1998 (Veenstra 2010) but not the contemporary fields of power of France and the UK.…”
Section: Resultsmentioning
confidence: 99%
“…One of us has variously embraced substantialism (Garnett et al 2008, Veenstra 2005, 2007b, Veenstra and Patterson 2012 and relationalism (Veenstra 2007a(Veenstra , 2009(Veenstra , 2010 in previous empirical implementations of aspects of Bourdieu's theory of practice and found the substantialist perspective and its associated methods by far the more familiar and straightforward. This indicates that upturning one's taken-for-granted ontological world-view and departing from prevailing doxa in health research is not easily accomplished.…”
Section: Resultsmentioning
confidence: 99%